Thermochemical and pore properties of goat-manure-derived biochars prepared from different pyrolysis temperatures - Touray, Njagga; Tsai, Wen-Tien; Chen, Huei-Ru; Liu, Sii-Chew (Journal of analytical and applied pyrolysis, 2014)
•Pyrolysis temperature had obvious influence on the thermochemical and porous characteristics.•The biochar yield decreased from 44.5 to 33.8% with temperature increased from 400 to 800°C.•The pyrolysis temperature of 800°C may be suitable for producing goat-manure-derived-biochar based on the thermochemical properties.•The maximum pore properties of goat-manure-derived-biochar appeared at round 800°C. In this work, goat manure (GM) was evaluated as a potential feedstock for preparing biochar. Its thermochemical characteristics were first investigated by the proximate analysis, calorific value, organic and mineral component analysis, showing that the biomass obviously comprises a large percentage of volatile matter and less amount of fixed carbon. A series of pyrolysis experiments were conducted to produce biochars (i.e., GMBC) from dry GM at different pyrolysis temperatures (673, 773, 873, 973, and 1073K) held for 30min. To evaluate their potential for soil amendment and energy use, the resulting biochars were subject to the analyses of chemical and physical properties, including proximate analysis, elemental analysis, calorific value, mineral components, true density, and surface area/pore volume. Based on the thermochemical properties, pyrolysis temperature at around 873K seemed to be suitable for the production of GMBC, where its calorific value (CV) (i.e., 16.28MJ/kg) only increased about 25% as compared to CV of the dry GM (i.e., 13.06MJ/kg). However, the temperature of around 1073K was found to be the pyrolysis conditions for producing porous carbon-like material with the maximal BET surface area (over 93m2g−1) and porosity (about 0.115).